Remaja Muslim di Pulau Mayoritas Katolik: Studi Hubungan Dukungan Sosial Dengan Kesejahteraan Psikologis pada Remaja di Kabupaten Lembata - Anggraeni Udjan, Febronia (Green Publisher Indonesia, 2024)
Psychological well-being discusses an individual's life journey that is going well. One of the factors that influences psychological well-being is social support. Social support is really needed by teenagers, therefore the focus of this research is on Muslim teenagers in Lembata Regency, where the majority of the population in Lembata Regency is Catholic. The aim of this research is to analyze the relationship between social support and psychological well-being. This type of research is quantitative research. Participants in this study were 96 teenagers who were taken using purposive sampling. Data collection techniques were carried out using a social support scale and a psychological well-being scale. Data analysis in this study used the SPSS for Windows version 23 program. The results showed that there was a relationship between social support and psychological well-being in Muslim adolescents in Lembata Regency, with a significant value of 0.000 (p<0.05) and a correlation coefficient of 0.589, which means there is positive and significant relationship between social support and psychological well-being in adolescents in Lembata Regency.